2009
DOI: 10.4269/ajtmh.2009.08-0662
|View full text |Cite
|
Sign up to set email alerts
|

A Temporal-Spatial Analysis of Malaria Transmission in Adama, Ethiopia

Abstract: Abstract. Urban malaria is a growing problem in Africa. Small-scale spatial studies are useful in identifying foci of malaria transmission in urban communities. A population-based cohort study comprising 8,088 individuals was conducted in Adama, Ethiopia. During a single malaria season, the Kulldorff scan statistic identified one temporally stable spatial malaria cluster within 350 m of a major Anopheles breeding site. Factors associated with malaria incidence were residential proximity to vector breeding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…From descriptive analysis, it was apparent that most of P. falciparium malaria have occurred nearer to the Dam, within two kilometer radius of GGHD and showed reduction with distance from Dam. This finding is in line with previous local studies [18],[43],[44] though the earlier findings were not reported in terms of plasmodium species composition. However, adjusting for the population density revealed the risk of P. falciparium infection was higher beyond one km radius of the Dam, especially in the buffer zone two to three km of the Dam.…”
Section: Discussionsupporting
confidence: 93%
“…From descriptive analysis, it was apparent that most of P. falciparium malaria have occurred nearer to the Dam, within two kilometer radius of GGHD and showed reduction with distance from Dam. This finding is in line with previous local studies [18],[43],[44] though the earlier findings were not reported in terms of plasmodium species composition. However, adjusting for the population density revealed the risk of P. falciparium infection was higher beyond one km radius of the Dam, especially in the buffer zone two to three km of the Dam.…”
Section: Discussionsupporting
confidence: 93%
“…From spearman rank correlation analysis minimum temperature (p=0.034) significant positively related with total malaria and with Plasmodium falciparum (p=0.030) which is similar with study in Adama [7], Jimma [8] and Burundi [6]. Maximum temperature (p=0.020) significantly negatively correlated with total malaria cases it is also the same as study in Jimma [8].…”
Section: Discussionsupporting
confidence: 75%
“…Large fields with loamy/clay soils tend to collect stagnant water from rivers and provide optimal conditions for anopheline breeding [32]. In Adama, Ethiopia, for example, households within 250 m of a floodplain have been shown to have a 22 times higher risk of contracting malaria than households further than 950 m away [33]. Sometimes it is the human activity associated with a setting that creates fertile conditions for vector breeding.…”
Section: Discussionmentioning
confidence: 99%